REFERENCE VALUES OF DRIS FOR THE SOYBEAN, cv. EMBRAPA 59 AND BR 37, IN CARAMBEÍ AT PARANÁ STATE, BRAZIL - MAEDA, Shizuo; RONZELLI Júnior, Pedro (Scientia Agraria, 2004)
Soil and leaves analysis to characterize the nutritional state of crops are usually interpreted on basis of optimal concentration ranges. This approach has been widely used for nutritional characterization of soybean in Brazil. However, the interpretation of analytical results for each nutrient in an isolated way without considering any hierarchy about nutritional limitations as well as possible effects of variety, sample age and local soil and climatic conditions has restricted its efficiency. To overcome part of these problems, the Diagnosis and Recommendation Integrated System (DRIS) appears as an alternative approach to the usual interpretation of nutritional state based on optimal concentration ranges. DRIS is also influenced by the same factors (i.e. variety, sample age etc) as for the concentrations range approach but in a lower degree. Such effects can be minimized by means of reference values, which are particularized to the factors that interfere in its magnitude and, therefore, in its efficiency. With the aim to obtain reference values of DRIS for soybeans in Carambeí, at Paraná state, Brazil, samples of leaves and grains were collected in areas of commercial soybeans crops during the growing season 1998-1999. The soybeans crops were cultivated using Embrapa 59 variety in a no-till system (SPD) and in a conventionaltill system (SPC), and also BR 37 variety in a SPD. Results from leaf samples and productivity of grains formed the database for the development of DRIS approach. The reference values obtained from Embrapa 59 and BR 37 varieties using SPD and SPC and from Embrapa 59 using SPC gave different estimations for the DRIS diagnosis indexes and, therefore, resulting in different diagnoses.